1999
DOI: 10.1177/146735849900100305
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Researching a Sensitive Issue: Gay Men, Sexuality Discrimination and the Hospitality Industry

Abstract: This paper outlines the methodological issues involved in the research of sexuality discrimination within the context of the hospitality industry. It draws upon a recently conducted study of sexuality discrimination among a small number of gay men in the hospitality industry. The theoretical and practical perspectives of a qualitative, interactionist methodology are explored; the philosophical issues of informed consent and confidentiality are outlined and set against the practicalities of conducting research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…If they thought in their mind that they were getting 'a gay waiter' they would have these instant thoughts of what this person would be like; which is wrong, but it could happen' (FG1M3). This is an interesting comment about what might happen and needs to be linked to actual experiences (in the research of Laffin (1999), for example) of when such stereotyping has occurred or may occur in these settings in order to be consolidate how this flirtatious encounter and possible stereotyping or discrimination of staff might impact the co-creation of hospitable experiences.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If they thought in their mind that they were getting 'a gay waiter' they would have these instant thoughts of what this person would be like; which is wrong, but it could happen' (FG1M3). This is an interesting comment about what might happen and needs to be linked to actual experiences (in the research of Laffin (1999), for example) of when such stereotyping has occurred or may occur in these settings in order to be consolidate how this flirtatious encounter and possible stereotyping or discrimination of staff might impact the co-creation of hospitable experiences.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Furthermore, it has been argued that the concept of sexuality has traditionally received very little attention in hospitality research and literature with regard to the discussion on the nature of sexualised labour prevalent in hospitality service work (Laffin, 1999; Lugosi, 2007a, 2007b; Markwell and Waitt, 2009; Vorobjovas-Pinta, 2018; Vorobjovas-Pinta and Dalla-Fontana, 2019; Ong et al, 2020). The research of Laffin (1999) indicated many ways in which openly gay staff had experienced forms of sexuality discrimination and homophobia, both in their working lives in the industry and also in their experience as consumers of the industry. Examples of discrimination that were cited included being passed over for promotion, impact of legislation, discrimination and treatment from guests and also their experience of being discriminated against as gay consumers in hotels.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It may be that gays and lesbians differ from other minority groups and wish to be perceived and accepted like the majority. Considering that as recently as the mid 1970s the American Psychological Association defined homosexuality as a mental disorder (Laffin 1999), it could be that homosexuals now wish to be perceived as "normal." Another possible explanation is that gays and lesbians want to feel that they are accepted as they are, and in the hotel context, this means mainly being able to sleep together and be treated as a couple.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth group is studies highlighting issues of discrimination. Laffin (1999), for example, suggested the existence of discrimination against gay employees in the hospitality industry. Finally, a growing area of research explores the sexual behavior of vacationing gay men in light of the HIV epidemic (e.g., Hawkes and Hart 1993;Clift and Forrest 1999a).…”
Section: Gay Men and Lesbians In Tourism Researchmentioning
confidence: 99%
“…There is a recognised difficulty in accessing informants when studying 'sensitive' issues (Laffin, 1999;Lee, 1993). Given the degree of disapproval and discrimination that is associated with homosexuality and the fact that some people will not openly acknowledge their sexual orientation it is impossible to ensure that any study is representative.…”
Section: Limitations and Further Researchmentioning
confidence: 99%